2020
DOI: 10.3390/ijms21207658
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Gold and Silver Nanoparticles with Bacterial Biofilms: Molecular Interactions behind Inhibition and Resistance

Abstract: Many bacteria have the capability to form a three-dimensional, strongly adherent network called ‘biofilm’. Biofilms provide adherence, resourcing nutrients and offer protection to bacterial cells. They are involved in pathogenesis, disease progression and resistance to almost all classical antibiotics. The need for new antimicrobial therapies has led to exploring applications of gold and silver nanoparticles against bacterial biofilms. These nanoparticles and their respective ions exert antimicrobial action by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 96 publications
6
128
0
Order By: Relevance
“…Even though our AgNPs showed lower inhibition of bacterial growth for the Gram-positive bacteria, they still showed a strong inhibitory effect on biofilm formation, even at the sub-MIC concentrations. These results suggest that lower concentrations of AgNPs do not directly damage the bacterial cells; however, the release of silver ions after dissolution of the nanoparticles might be able to inhibit biofilm formation by altering gene expression or inhibiting quorum sensing within the biofilm 49 . It has been previously shown that the antibacterial activity of AgNPs is strongly correlated with their size.…”
Section: Discussionmentioning
confidence: 92%
“…Even though our AgNPs showed lower inhibition of bacterial growth for the Gram-positive bacteria, they still showed a strong inhibitory effect on biofilm formation, even at the sub-MIC concentrations. These results suggest that lower concentrations of AgNPs do not directly damage the bacterial cells; however, the release of silver ions after dissolution of the nanoparticles might be able to inhibit biofilm formation by altering gene expression or inhibiting quorum sensing within the biofilm 49 . It has been previously shown that the antibacterial activity of AgNPs is strongly correlated with their size.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, both their size and morphology were not altered when introduced into the bacterial culture medium. According to the literature, four to seven different mechanisms of action for MNPs as an antibacterial agent are described [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. For example, Lee and Jun described four main routes of antibacterial mechanism of AgNPs, namely (i) adhesion to the cell membrane, (ii) penetration onside the cell, (iii) ROS generation and cellular toxicity, and (iv) genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee and Jun described four main routes of antibacterial mechanism of AgNPs, namely (i) adhesion to the cell membrane, (ii) penetration onside the cell, (iii) ROS generation and cellular toxicity, and (iv) genotoxicity. In a more recent review, Joshi et al, listed seven different mechanisms of action: (i) Disruption of cell membrane, (ii) destabilization and disruption of membrane proteins, (iii) destabilization and disruption of cytoplasmic proteins, (iv) inactivation of enzymes and metabolic interference, (v) generation of ROS, (vi) damage to DNA and ribosomal assembly, and (vii) impairment in transmembrane electron transport system [ 34 ]. It is worth noticing they can be coupled with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many solutions that can improve the efficiency of aPDT against Gram-negative bacteria, there is great interest in the use of photosensitizers in combination with metal nanoparticles, because nanoparticles have been shown to be able to pass through the cell walls of both Gram-negative and Gram-positive bacteria [ 17 ]. Currently, several options for photosensitizers are present in the literature, and it has been shown that their combination with metallic nanoparticles is a promising strategy for improving antimicrobial activity [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%